2005
DOI: 10.1016/j.mod.2004.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A cytokine secreted from the suboesophageal body is essential for morphogenesis of the insect head

Abstract: The suboesophageal body of insects was identified over a century ago in the silkworm embryo, but its biological function is still unknown. We discovered that this tissue is differentiated in the earliest embryonic stages of the cabbage armyworm and secretes the insect cytokine, growth-blocking peptide (GBP), transiently from 24 to 60 h after oviposition when gastrulation is in progress. Over-expression of GBP, achieved by microinjection of the GBP gene driven by a cytomegalovirus (CMV) constitutive promoter, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…They have diverse functions such as growth retardation1112, paralysis induction131516, cardioacceleration16, cell proliferation2526, embryogenic morphogenesis27, and immune cell stimulation1428. Characterization of some of these peptide cDNAs demonstrated that the ENF peptides are synthesized as a precursor form in which the active peptide is located at the C-terminal region15282930.…”
mentioning
confidence: 99%
“…They have diverse functions such as growth retardation1112, paralysis induction131516, cardioacceleration16, cell proliferation2526, embryogenic morphogenesis27, and immune cell stimulation1428. Characterization of some of these peptide cDNAs demonstrated that the ENF peptides are synthesized as a precursor form in which the active peptide is located at the C-terminal region15282930.…”
mentioning
confidence: 99%
“…Genetic analysis of Drosophila should allow us to determine the function of these peptides using tools that were not available when GBP was studied in Lepidopterans. There is growing evidence that the ENF cytokine family member GBP plays a crucial role in maintaining insect life from embryonic to larval stages (Tsuzuki et al, 2005a(Tsuzuki et al, , 2005b. The many functions of GBPs include morphogenesis, cellular immunity, cardiomotility and larval growth regulation.…”
Section: Discussionmentioning
confidence: 99%
“…1). Indeed, we have already shown that the ENF peptide gene of M. brassicae plays an essential role on the morphogenesis of the embryonic head portion (30). Additionally, when a higher proportion of PP protein is required for any purpose, it can be achieved by co-expressing the protein from the monocistronic PP mRNA, which was detected throughout the embryogenesis and larval development (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained genomic sequences were deposited in the GenBank TM /EMBL/DDBJ databases (accession numbers AB511039, AB511041, and AB511042). The ENF peptide gene sequences of the P. separata (number AB012294) (28) and M. brassicae (AB126696) (30) were also used for analyzing the genomic structure of the uENF1-uENF 2- PP ( ENF peptide) mRNA of the two moths.…”
Section: Methodsmentioning
confidence: 99%